Comparative Analysis Of AHP With TOPSIS In The selection Of New Student Majors At The Universitas Nasional: Comparative Analysis Of AHP With TOPSIS In The selection Of New Student Majors At The Universitas Nasional - Febfiyana Febfiyana; Septi Andryana; Deny Hidayatullah (Institute of Computer Science (IOCS), 2020)
Every year high school graduates / equivalent have the desire to continue Reviews their education to a higher level one of them at the National University roomates study has many programs but there are some obstacles faced by graduates that are still not knowing what programs are Appropriate study. With this the researcher Utilizes a decision support system designed by applying the Technique for Order Preference by Similary to Ideal Solution (TOPSIS) method is then roomates Compared to the Analytical Hierarchy Process (AHP) method. So the results of system design are Able to help in finding and Determining the Appropriate study program. The results of the comparison based on the level of suitability are 10:12% for the AHP method and 98.84% for the TOPSIS method.